Pemahaman Matematis Siswa Pada Materi Pola Bilangan di SMP Tamansiswa Pematang Siantar - Asmara Ramadhan; Firman Pangaribuan; Gayus Simarmata (CV Putra Publisher, 2024)
The purpose of this research is to determine students' mathematical understanding of number pattern material at Tamansiswa Pematang Siantar Middle School. The results of this research can be concluded that students who have high comprehension abilities can solve questions accurately and correctly. Then you can solve it by writing down what is known and asked about the problem and being able to understand the concept of number patterns and number pattern facts in terms of simple concepts. Students who have high understanding meet all 4 indicators of mathematical understanding that have been selected by researchers. Students who have moderate understanding can solve problems on questions and are able to understand the concept of number patterns and number pattern facts in terms of simple concepts. However, students who had low understanding did not understand the questions given by the researcher. And students who have moderate understanding fulfill 2 indicators of mathematical understanding. Students who have low understanding are unable to understand the problem, cannot state that they know and are asked about a problem, are unable to solve the problem and are unable to complete the operation of the requested problem. The student was very confused in solving the questions, this was proven by the difference in what the question asked for and what he answered and was unable to convey the concepts of number patterns. Students who have low understanding only fulfill 1 indicator of mathematical understanding.